Comparative exercises on “madness” in the Argentinean Chaco - Tola, Florencia (2020)
This paper tries to carry out a comparative exercise between the comparisons made by me and those made by the Toba people (qom) of the Argentinean Chaco. I will try to elucidate the tools with which they and I made these comparisons possible. I will refer to three events that occurred during my fieldwork carried out from 1997 to the present. These cases are related to the context of that we may call as “madness”, and that have ontological implications. The events show the contrasts explained by my indigenous interlocutors between a non indigenous and a qom way of conceiving madness-becoming-other. These ethnographic cases will allow us to reflect upon the challenges involved in concentrating on the quid of the comparison from the Toba point of view.